"You Better Move On": Determinants and Labor Market Outcomes of Graduate Migration from Italy. Issue 1 (March 2019) - Assirelli, Giulia; Barone, Carlo; Recchi, Ettore
After the Eurozone crisis, out-migration from southern Europe revived, mostly fed by the highly skilled young. Nevertheless, little is known about these new migrants, particularly regarding the determinants and payoffs of their moves. This study delves into the Italian case, drawing on a large representative sample of the 2011 graduation cohort. Multivariate analyses show that young people from upper-class families, foreign citizens, graduates in scientific and internationally oriented fields, and best-performing students are more likely to migrate. Moreover, compared to the "stayers, " graduate migrants enjoy more favorable outcomes in terms of wages, unemployment risks, access to skilled employment, and career satisfaction.